التنمية البشرية في ضوء السيرة النبوية (التنمية القيادية والإدارية نموذجاً): Personality Development in the Light of Al-Sirah Al-Nabwiyyah: (Leadership and management development) - Dr. Hamid Ashraf Hamdani (Seerat Studies, 2023)
This research paper deals with the concept of development and the interest of the Prophet (SAW) about up-grading his companions’ capabilities in all aspects. It consists of three parts with conclusion. The first part discusses the definition of human development and its most prominent characteristics in Islamic perspective. The second and third parts has focuse on leadership development and management. It also deals with the required skills for each. This research paper concludes some important findings and recommendations for onward future career of every individual and society under the light of S┘rat Al-Nabi (SAW).